DIGITAL MARKETING COMMUNICATION STRATEGY PT TAMBANG CULINARY NUSANTARA MADIUN OUTLET: DIGITAL MARKETING COMMUNICATION STRATEGY PT TAMBANG CULINARY NUSANTARA MADIUN OUTLET - Amadea Ayuningtyas, Shakila; Supriyanto, Muhammad (Epicheirisi: Jurnal Manajemen, Administrasi, Pemasaran dan Kesekretariatan, 2025)
This Final Project research aims to find out the digital marketing communication strategy through Instagram social media of PT Tambang Kuliner Nusantara Outlet Madiun. This research uses a qualitative descriptive approach method based on Chaffey & Chadwick's (2017) theory of the RACE (Reach, Act, Convert, Engage) Framework. Data collection was carried out through interviews, observation, and documentation with three informants. Data were processed and presented in the form of exposure and discussion. The final results of the study show that the digital marketing communication strategy implemented by PT Tambang Kuliner Nusantara is effective in increasing marketing and sales of the company's products.